'Improving the odds for everybody': Narrative and media in stem cell donor recruitment patient appeals, and the work to redress racial inequity. Issue 7 (5th August 2022) - Williams, Ros
Abstract: Stem cell registries, which provide cells for transplants in blood malignancy treatment, recruit donors partly through mobilising narrative. This is often via appeals from patients without matching donors who seek to encourage registrations from people who might go on to be their own, or somebody else's, donor. Registries have also historically underserved racially minoritised communities, who are less likely to locate matching donors. As such, appeals often come from racially minoritised patients. Prior research highlights the importance of narrative in health contexts, and donation in particular. However, the impact of stories on those telling them is underexplored. This article fills this gap, providing analysis of a range of interview, media and documentary data. It sketches out the contours of appeal work, showing how patients' private lives become publicly exposed. It highlights how appeals might be understood as collective action on behalf of racially minoritised communities, flagging how those most affected by inequity often become central to the fight to redress it. Through this, the article extends an emergent 'sociology of donation', arguing for acknowledgement of media's importance in contemporary donation contexts.